The Need for Inspirational (Charismatic) Teachers in Today's Classrooms. - Qardaku, Nevila Gurra (European Journal of Multidisciplinary Studies, 2019)
In the time when access to diversified and abundant information by high school students is very easy, where a student in his comfortable home via the internet, can find quick answers to his questions without having to go and stay in the class with many rules, the need for inspirational teachers is felt more than ever. The increasing number of students who do not respect the treasured figure of the teacher, and under the circumstances when the number of elements that serve as magnets to attract the students' wishes and attention at the expense of school education has increased more than ever, inspirational teachers are needed to increase the curiosity and need of the learner to explore with curiosity. The purpose of this paper is to explain the influence that inspirational teachers have on their students, based on the literature review. Conclusions: inspirational teachers are experts in their subject. They transmit enthusiasm, cultivate positive relationships with students. They are flexible, reflective and adapt to their practices, make intentional and meaningful learning for students. They also help their students to discover where their talents combine with their passions, promote a safe and stimulating climate (environment) in the classroom, create a clear and positive classroom management, developes collaboration and brings innovation to the classroom. This reflection serves to all the actors of education.
Keywords: Inspirational teachers (charismatic), today's classrooms, high school students, curiosity, expert.